Symposium 10: Communication and Control in E-Learning Environments Symposium: Symposium Introduction - Mann, Sarah J. (Proceedings of the International Conference on Networked Learning, 2004)
The purpose of this Symposium is to present the work of the Communication and Control in E-Learning Environments Special Interest Group (SIG) of the Equality in E-Learning Project. The SIG has examined the inter-relationships between on-line communication and learner and tutor experience of control over different aspects of the e-learning process. If education is seen as a prime site for the reproduction of reality, the interaction of asymmetrical power relations between teachers and students, and the formation of identities, then understanding issues of communication and control becomes central to an understanding of educational processes. E-learning and in particular networked, collaborative e-learning, provides a very interesting case study. It offers, in its processes and in its philosophical approach, an understanding of reality as constructed and an approach which supports the construction of alternative ‘realities’ (i.e. it challenges the idea of truth as naturalized); it aims to engage learners and teachers in collaborative and social processes where the aim is to reduce the unequal distribution of power between participants; and it supports subjectivity and takes account of difference and the expression and construction of multiple identities. It is also embedded within new forms of communication technology which may enable or constrain these processes. The interesting question posed by this new learning process is: what happens to communication and control within such new contexts of learning?